PFunkel: efficient, expansive, user-defined mutagenesis. - Elad Firnberg; Marc Ostermeier (PLoS ONE, 2012)
We introduce PFunkel, a versatile method for extensive, researcher-defined DNA mutagenesis using a ssDNA or dsDNA template. Once the template DNA is prepared, the method can be completed in a single day in a single tube, and requires no intermediate DNA purification or sub-cloning. PFunkel can be used for site-directed mutagenesis at an efficiency approaching 100%. More importantly, PFunkel allows researchers the unparalleled ability to efficiently construct user-defined libraries. We demonstrate the creation of a library with site-saturation at four distal sites simultaneously at 70% efficiency. We also employ PFunkel to create a comprehensive codon mutagenesis library of the TEM-1 ß-lactamase gene. We designed this library to contain 18,081 members, one for each possible codon substitution in the gene (287 positions in TEM-1 x 63 possible codon substitutions). Deep sequencing revealed that ∼97% of the designed single codon substitutions are present in the library. From such a library we identified 18 previously unreported adaptive mutations that each confer resistance to the ß-lactamase inhibitor tazobactam. Three of these mutations confer resistance equal to or higher than that of the most resistant reported TEM-1 allele and have the potential to emerge clinically.